Implementation of Khidmah Program in Improving the Performance of Khidmah Teachers at Pondok Pesantren Mamba'ul Ulum Dukuh Mencek Jember - Ahmad Shodiq; Imron Fauzi; St Rodliyah (South Sulawesi Education Development (SSED), 2024)
Khidmah is a feasibility test for all that has been experienced by santri. The pesantren attempts to place its vision and work within the framework of social khidmah, which initially emphasises the formation of religious values and then develops into more integrated and systematic development pilots. This research uses qualitative methods. The data collection techniques and procedures used in this research are observation, interview and documentation. Researchers used descriptive analysis by describing the tracking process and explaining the results of the data obtained. The data that has been collected is then analysed in accordance with the research, the next stage is concluded with language that is easy to understand and understand. The data obtained is then analysed descriptively to obtain the final conclusion.